2003
DOI: 10.1063/1.1578182
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiative and structural properties of 1.3 μm InxGa(1−x)As quantum-dot laser structures grown by metalorganic chemical vapor deposition and molecular-beam epitaxy: Effect on the lasing properties

Abstract: Electrically injected InGaAs/GaAs quantum-dot microcavity light-emitting diode operating at 1.3 μm and grown by metalorganic chemical vapor deposition Appl. Phys. Lett. 84, 4155 (2004); 10.1063/1.1755411 Dependence of the emission wavelength on the internal electric field in quantum-dot laser structures grown by metal-organic chemical-vapor deposition Appl. Phys. Lett. 79, 1435 (2001); 10.1063/1.1400088 Room-temperature 1.3 μm emission from InAs quantum dots grown by metal organic chemical vapor deposition Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…This can be caused by EL from excited states or even by EL from states in the SRL based quantum well (QW). The larger built-in dipole in MOVPE prepared QDs prevents lasing from the ground state, allowing emission only from the excited states [1]. A variety of theoretical [2] and experimental [1,3,4] studies have recently reported the existence of permanent electron-hole dipole moment in QDs, which is related to the shape and strain field of QDs.…”
Section: Introductionmentioning
confidence: 98%
“…This can be caused by EL from excited states or even by EL from states in the SRL based quantum well (QW). The larger built-in dipole in MOVPE prepared QDs prevents lasing from the ground state, allowing emission only from the excited states [1]. A variety of theoretical [2] and experimental [1,3,4] studies have recently reported the existence of permanent electron-hole dipole moment in QDs, which is related to the shape and strain field of QDs.…”
Section: Introductionmentioning
confidence: 98%
“…Although remarkable progress [1][2][3][4][5][6] has been reported, such as a very low threshold current density (16 A/cm 2 ) [4] and a very high characteristic temperature (320 K) [5], these achievements were made with QD lasers grown by molecular beam epitaxy (MBE). In comparison, the advance in QD lasers fabricated by metalorganic chemical vapor deposition (MOCVD) lags behind that by MBE, and the performance of QD lasers by MOCVD [7][8][9][10][11][12][13] is far inferior to those by MBE [5][6][7]. In terms of high growth rates in mass production requirement or application to optical integrated devices that require regrowth or selective area growth, it would be greatly beneficial to realize QD lasers fabricated by MOCVD.…”
Section: Introductionmentioning
confidence: 97%
“…Although remarkable progress [1-6] has been reported, such as a very low threshold current density (16 A/cm 2 ) [4] and a very high characteristic temperature (320 K) [5], these achievements were made with QD lasers grown by molecular beam epitaxy (MBE). In comparison, the advance in QD lasers fabricated by metalorganic chemical vapor deposition (MOCVD) lags behind that by MBE, and the performance of QD lasers by MOCVD [7-13] is far inferior to those by MBE [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In QD growth, the growth temperature is usually low in order to suppress surface migration and enhance dot formation. In metalorganic vapor phase epitaxy (MOVPE) growth of QD, low growth temperature results in other problems like insufficient pyrolysis of precursors [6,7]. In order to testify the concept of Alenhanced QD formation and improve QD density in MOVPE growth, we performed AlGaInAs QD growth on GaAs substrate.…”
Section: Introductionmentioning
confidence: 99%